Methods of psychological intervention - Sammut, Gordon; Foster, Juliet L. H.; Salvatore, Sergio; Andrisano-Ruggieri, Ruggero (YIS (Series) ;, 2016)
Methods of Psychological Intervention provides a rich collection of chapters that provide an invaluable resource to scholars, researchers and practitioners in psychology. Psychological interventions are becoming increasingly popular in contemporary societies. This volume is intended to help psychologists and other professionals understand how general psychological knowledge can serve to guide local and particular interventions. The present volume helps bridge the gap between general knowledge in the psychological sciences and particular instances of human behavior as it takes place in everyday life.The volume forms part of the series 'Yearbook of Idiographic Science'. Authors draw on principles of idiographic science to formulate interventions applicable to a broad diversity of settings and institutions, such as educational settings, organizations, and medical settings. It similarly deals with various psychological behaviours targeted for intervention, such as gambling, family therapy, and crime. The volume will be of interest to scholars, researchers and practitioners working in the fields of psychology, social work, counseling, family therapy, education, organizational behavior & criminal justice.